A phosphoinositide 3-kinase/phospholipase cgamma1 pathway regulates fibroblast growth factor-induced capillary tube formation - Maffucci, T.; Raimondi, C.; Abu-Hayyeh, S.; Dominguez, V.; Sala, G.; Zachary, I.; Falasca, Marco (Public Library of Science, 2009)
Background: The fibroblast growth factors (FGFs) are key regulators of embryonic development, tissue homeostasis and tumour angiogenesis. Binding of FGFs to their receptor(s) results in activation of several intracellular signalling cascades including phosphoinositide 3-kinase (PI3K) and phospholipase C (PLC)?1. Here we investigated the basic FGF (FGF-2)-mediated activation of these enzymes in human umbilical vein endothelial cells (HUVECs) and defined their role in FGF-2-dependent cellular functions. Methodology/Principal Findings: We show that FGF-2 activates PLC?1 in HUVECs measured by analysis of total inositol phosphates production upon metabolic labelling of cells and intracellular calcium increase. We further demonstrate that FGF-2 activates PI3K, assessed by analysing accumulation of its lipid product phosphatidylinositol-3,4,5-P3 using TLC and confocal microscopy analysis. PI3K activity is required for FGF-2-induced PLCc1 activation and the PI3K/PLCc1 pathway is involved in FGF-2-dependent cell migration, determined using Transwell assay, and in FGF-2-induced capillary tube formation (tubulogenesis assays in vitro). Finally we show that PI3K-dependent PLC?1 activation regulates FGF-2-mediated phosphorylation of Akt at its residue Ser473, determined by Western blotting analysis. This occurs through protein kinase C (PKC)a activation since dowregulation of PKCa expression using specific siRNA or blockade of its activity using chemical inhibition affects the FGF-2-dependent Ser473 Akt phosphorylation. Furthermore inhibition of PKCa blocks FGF-2-dependent cell migration. Conclusion/Significance: These data elucidate the role of PLC?1 in FGF-2 signalling in HUVECs demonstrating its key role in FGF-2-dependent tubulogenesis. Furthermore these data unveil a novel role for PLC?1 as a mediator of PI3K-dependent Akt activation and as a novel key regulator of different Akt-dependent processes. a 2009 Maffucci et al.